Multi-suspension reversible equipment and devices for carrying children - JIN YANDONG (2017)
The invention relates to multi-suspension reversible equipment and devices for carrying children. The multi-suspension reversible equipment and devices comprise a vehicle frame, wheels mounted on the vehicle frame and a sitting and lying device used for allowing an infant to sit and lie down. The sitting and lying device has the forward using position and the backward using position. The two sides of the sitting and lying device are hinged to the vehicle frame through at least two connecting rod assemblies. The vehicle frame comprises a first vehicle frame body and a second vehicle frame body which are hinged to each other. According to the sitting and lying device, one end of a first seat support, a seat left-inner connecting rod, a seat left-outer connecting rod and one end of a second seat support are hinged in sequence through a first seat shaft, a second seat shaft, a third seat shaft and a fourth seat shaft, the other end of the first seat support, a seat right-inner connecting rod, a seat right-outer c